Increasing trend of endoscopic drainage utilization for the management of pancreatic pseudocyst: insights from a nationwide database - Khaled Elfert; Salomon Chamay; Lamin Dos Santos; Mouhand Mohamed; Azizullah Beran; Fouad Jaber; Hazem Abosheaishaa; Suresh Nayudu; Sammy Ho (Korean Society of Gastrointestinal Endoscopy, 2024)
Background/Aims The pancreatic pseudocyst (PP) is a type of fluid collection that typically develops as a delayed complication of acute pancreatitis. Drainage is indicated for symptomatic patients and/or associated complications, such as infection and bleeding. Drainage modalities include percutaneous, endoscopic, laparoscopic, and open drainage. This study aimed to assess trends in the utilization of different drainage modalities for treating PP from 2016 to 2020. The trends in mortality, mean length of hospital stay, and mean hospitalization costs were also assessed. Methods The National Inpatient Sample database was used to obtain data. The variables were generated using International Classification of Diseases-10 diagnostic and procedural codes. Results Endoscopic drainage was the most commonly used drainage modality in 2018-2020, with an increasing trend over time (385 procedures in 2018 to 515 in 2020; p=0.003). This is associated with a decrease in the use of other drainage modalities. A decrease in the hospitalization cost for PP requiring drainage was also noted (29,318 United States dollar [USD] in 2016 to 18,087 USD in 2020, p<0.001). Conclusions Endoscopic drainage is becoming the most commonly used modality for the treatment of PP in hospitals located in the US. This new trend is associated with decreasing hospitalization costs.